Green Intellectual Capital and Carbon Performance: The Moderating Role of Audit Quality - Ulfa Rahmawati; Lely Kumalawati (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to examine the effect of Green Intellectual Capital (GIC) on carbon performance and to investigate the moderating role of audit quality in this relationship. The study employs panel data from firms from 2023 to 2024. The analysis is conducted using a panel data regression approach with a Random Effect Model (REM) and robust standard errors. The results indicate that Green Intellectual Capital does not have a significant effect on carbon performance. Furthermore, audit quality is not found to moderate the relationship between Green Intellectual Capital and carbon performance. These findings suggest that both internal capabilities and external monitoring mechanisms are insufficient to enhance a firm's carbon performance. The implications of this study highlight the need for more substantive environmental practices and stronger regulatory frameworks to improve carbon performance.